Ciclo diario y anual de variables troposféricas y oceánicas en la Isla del Coco, Costa Rica - Alfaro, Eric J. (Revista de Biología Tropical, 2008)
Diel and annual cycle of tropospheric and oceanic variables in Cocos Island, Costa Rica. Meteorological records from gauge stations at Isla del Coco (Cocos Island), Costa Rica, were analyzed. These data are from an automatic weather station and from two pluviograph stations, covering the period 1997-2005. Time series from other historical records and from the nearest island grid point from different public geophysical data sets were also used. The focus was on rainfall, wind, radiation, relative humidity, and air and sea temperature series. Daily and annual cycles were calculated for all the records with hourly resolution and their intraseasonal features were studied, such as maxima values, minima values and transitional periods. Comparisons were done between the stations records and the grid (with broader spatial resolution data). In general, seasonal variations at Isla del Coco were observed to be mainly associated with the meridian migration of the Inter Tropical Convergence Zone; the island is under its direct influence from boreal spring to autumn. Rev. Biol. Trop. 56 (Suppl. 2): 19-29. Epub 2008 August 29.